The strategic role of cleanliness in enhancing service quality: a case of green world hotel zhongxiao taipei - Erna Wigati; Henny Kustini; Anggi Bayu Pradana (Journal of Gastro Tourism, 2026)
This research aims to analyse the role of cleanliness in supporting service quality at Green World Hotel Zhongxiao, Taipei, Taiwan. The research methodology used is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research focuses on the implementation of cleanliness standard operating procedures (SOPs) by the hotel post-pandemic recovery challengges. The research results show that Green World Hotel Zhongxiao has optimally implemented cleanliness thru the use of cleaning tools according to the hotel's established SOPs, periodic cleaning of hotel areas, monthly disinfectant spraying, and regular monthly evaluation meetings with all hotel staff. In addition, guest rooms are cleaned according to applicable SOPs, and all hotel facilities are cleaned periodically to maintain cleanliness and guest comfort standards. Therefore, cleanliness plays a significant role in maintaining the quality of service and the hotel's positive image at Green World Hotel Zhongxiao.